Keragaan dan Potensi Produksi Varietas Unggul Baru Padi pada Lahan Sawah Bukaan Baru Keracunan Besi - Busyra Buyung Saidi; Jon Hendri; Suharyon Suharyon (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Saidi BB, Hendri J, Suharyon S. 2020. Performance and production potential yield of new rice high yielding varieties on new constructed irrigated rice field of iron poisoning fields. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xxx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Assessment of Performance and Potential Yields of New Rice High Yielding Varieties on New Constructed Irrigated Rice Field of Iron Poisoning Fields was carried out in Muntialo Village, Betara District, Tanjung Jabung Barat Regency from April to August 2018. The rice varieties used consisted of: 4 varieties, namely (1) Inpari 34 Agritan Salin, (2) Inpara 3, (3) Indragiri, and (4) IR 42. The study used a randomized block design with 4 (four) replications. Fertilization recommendations based on soil nutrient status. Cultivation of crops with an integrated crop management system (ICM) of Swamp Rice. 4: 1 legowo planting system with 20 days of seedlings. The data collected consisted of the chemical properties of the soil before the assessment, components of plant growth and production. The results showed that there was no significant difference in plant height between the varieties tested. The highest plant height was Inpari 34 (105.37 cm) and Inpara 3 (100.98 cm), followed by Indragiri (97.73 cm) and the lowest was IR 42 (93.38 cm). There was a significant difference between the maximum number of tillers, productive tillers, the number of grains per panicle and yield of harvested dry grain between the VUB tested. The highest production was obtained by Inpari 34 (5.58 tons/ha), while Inpara 3 (4.10 tons/ha), Indragiri 3.86 tons / ha and the lowest was on IR 42 (3.40 tons/ha).